The Role of Labor Courts in Restoring Workers' Rights - Jalal, Iman Safaa Al-Din Jalal (Sulaimani Journal for Humanities, 2025)
The right to work is an important right enshrined in the Second Covenant onEconomic, Social and Cultural Rights (1966) and states are obliged to take appropriate measures to protect this right, including the right to enjoy fair and satisfactory workingconditions which commensurate with the value of the worker labour and providing foroccupational safety and health. The purpose of this study, which is entitled (The Role of Labour Courts in Recovering Workers’ Rights - An Analytical Study - Sulaymaniyah Governorate Labour Court/Iraq - as a Sample), is to understand the level of work and stability of workers and employers play an important role in ensuring that each complies with their rights and obligations in labour relations. Moreover, the study focuses on the role of labour courts in filing and deciding any claims against workers or employers according to the applicable laws in the Kurdistan Region. To achieve the main objective of the research,(the researchers) relied on a descriptiveanalytical approach to answer the main question, which is : To what extent does the Labour Court play a role in restoring workers' rights in the labour market in Sulaimani province?, the research was divided into three parts: the first part deals with the nature and importance of labour courts, the second part deals with the concept of workers and their rights. The third part dealt with (the field aspect of the research) which investigates the restoration of workers' rights in the labour courts in Sulaimani province. Through our analysis of various aspects related to labour rights and laws implemented in the Kurdistan Region/Iraq, the study reached several conclusions, including: The study concluded that the judges have been able to restore workers' rights to a good extent, as evidenced by the number of lawsuits received in 2023 and resolved in the same year. Despite the benefits of Labour Law No. 37 of 2015 and the draft labour law in the Kurdistan Region dated 23/10/2022, there are some remarks on both of them)
Keywords: Labor courts; workers rights; Kurdistan RegionIraq